2005
DOI: 10.1111/j.1464-5491.2005.01601.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of angiotensin‐converting enzyme DD genotype with 24‐h blood pressure abnormalities in normoalbuminuric children and adolescents with Type 1 diabetes

Abstract: Children and adolescents with Type 1 diabetes do not differ from the non-diabetic population regarding the I/D polymorphism of the ACE gene. ACE gene polymorphism is associated with BP abnormalities in normotensive and normoalbuminuric children and adolescents with Type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…This observation has been confirmed in many studies conducted in the general population and among subjects with T2DM [6, 27, 28]. Studies performed in the pediatric population have shown that allele DD in ACE polymorphism is associated with higher BP in normotensive, normoalbuminuric diabetic children in ABPM measurements [9, 29]. Similarly in our previous study, when we have taken into account only clinically normotensive and normoalbuminuric children, we have proven that subjects in the DD genotype group had significantly higher nocturnal BP in comparison with ID/II genotype group, and this was also connected with lower dipping [10].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This observation has been confirmed in many studies conducted in the general population and among subjects with T2DM [6, 27, 28]. Studies performed in the pediatric population have shown that allele DD in ACE polymorphism is associated with higher BP in normotensive, normoalbuminuric diabetic children in ABPM measurements [9, 29]. Similarly in our previous study, when we have taken into account only clinically normotensive and normoalbuminuric children, we have proven that subjects in the DD genotype group had significantly higher nocturnal BP in comparison with ID/II genotype group, and this was also connected with lower dipping [10].…”
Section: Discussionsupporting
confidence: 52%
“…These polymorphisms were selected for the study based on evidence from the literature. The best known gene variant association in the ACE genes is I/D variant, with allele DD connected with potentially higher BP [4, 6, 9, 10]. Moreover, we chose to study another two single nucleotide polymorphisms (SNP) of ACE , rs1800764 and rs4459609, because they were shown to characterize the haplotypic structure of ACE in European populations [18, 19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…But it is possible to speculate that the DD genotype may provide resistance against the development of sepsis. This may be explained by the characteristics of the individuals who have the DD genotype, because they have higher systolic blood pressure levels than those with other ACE genotypes 16,17 . The lower blood pressure will generate a lower volume of blood in the peripheral parts of the body; therefore, cells will not receive enough oxygen and nutrients, and waste products will not be adequately removed, which may subsequently facilitate the development of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In the paediatric population, there is little information on the association of polymorphisms in the RAS and the development of early signs of microvascular complications. Some have demonstrated that ACE gene polymorphism is associated with BP abnormalities in normotensive and normoalbuminuric children with T1DM (40).…”
Section: Genetic Factorsmentioning
confidence: 99%